Distinct roles of C2A and C2B domains of synaptotagmin in the regulation of exocytosis in adrenal chromaffin cells - Ohara-Imaizumi, Mica (The National Academy of Sciences of the USA, 1997)
Synaptotagmin that contains two repeats of C2 regulatory domains is considered to be involved in neurotransmitter release. To reveal the roles of synaptotagmin in the regulation of exocytosis, we examined the effects of antibodies against C2A and C2B domains on Ca(2+)-evoked catecholamine (CA) release from digitonin-permeabilized adrenal chromaffin cells, resolving the Ca(2+)-evoked release into ATP-dependent priming and ATP-independent Ca(2+)-triggered steps. Anti-C2A antibody clearly reduced the ATP-independent release, suggesting that the C2A domain directly facilitate or promote Ca(2+)-triggered step, vesicular fusion. In contrast, anti-C2B antibody did not affect Ca(2+)-evoked release by itself, but significantly increased the spontaneous Ca(2+)-independent release. In addition, inositol high-polyphosphate series (IHPS) that bind the C2B domain inhibited both the ATP-independent Ca(2+)-evoked release and the spontaneous release in a dose-dependent manner. The inhibition by IHPS was totally reversed by anti-C2B antibody and significantly reversed by high concentration of Ca(2+). These results suggest that IHPS binding to C2B domain arrests membrane fusion by presumably preventing interaction of synaptotagmin with phospholipids or with proteins of plasma membrane. Thus, IHPS binding to the C2B domain might keep the docked or primed vesicles away from spontaneous fusion at resting level of intracellular Ca(2+). Binding of the increased intracellular Ca(2+) to the C2A domain may facilitate or trigger the vesicular fusion by releasing this suppression by IHPS.